# verify x3+y3=(x+y)(x2-xy+y2)

Hii,

Q). Verify that x3 + y3 = (x+y) ( x- xy + y2)

1).  R.H.S => (x+y) ( x2 - xy + y2)
=> x3 - x2y + xy2 + x2y - xy2 + y3                  {On multiplying x3 + y3 with (x+y) ( x2 - xy + y2)}
=> [x3 + y3] + ( -x2y + x2y) + ( xy2 - xy2)
=>  x3 + y3
Since R.H.S = L.H.S,
That is x3 + y3 = x3 + y3
Hence, verified that x3 + y3 = (x+y) ( x- xy + y2)

OR
2). L.H.S => Using identities.. (a3 + b3) = (a+b)(a2 - ab +b2)
=> (x+y) [(x)2 - ( x * y ) + (y)2]
=> (x+y) ( x2 - xy + y2)
Since, L.H.S = R.H.S,
that is  (x+y) ( x2 - xy + y2) = (x+y) ( x2 - xy + y2)
Hence verified that x3 + y3 = (x+y) ( x2 - xy + y2)

Although, for verifying the first step is mostly used !

Hope this helps ! :)

• 24
Take your ncert book and find har cheez puchne ke liye nhi hoti ok. Kuch cheeze kudh se bhi dhundni pdti now. Find it aur meritnation pr.comab kbhi mt aana bkwaas app hai . Now just get lost.
• -14
Take your ncert book and find har cheez puchne ke liye nhi hoti ok. Kuch cheeze kudh se bhi dhundni pdti now. Find it aur meritnation pr.comab kbhi mt aana bkwaas app hai . Now just get lost
• -13
RHS= (x+y)(x2- xy +y2)
Open the brackets so,
x3-x2y+xy​2+x2y-xy2+y3
By simplfying,( ​-x2y+xy​2+x2y-xy2) becomes 0
So,
x3+y3
Hence proved
• 5
Very easy question first try youself dont see ans. If wrong come and see answer
• -3
What are you looking for?